2022
DOI: 10.1136/thoraxjnl-2021-217994
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in sputum and blood inflammatory mediators during FeNO suppression testing

Abstract: To explore whether fractional exhaled nitric oxide (FeNO) non-suppression identifies corticosteroid resistance, we analysed inflammatory mediator changes during a FeNO suppression test with monitored high-intensity corticosteroid therapy. In linear mixed-effects models analysed over time, the 15 clinically distinct ‘suppressors’ (ie, ≥42% FeNO suppression) normalised Asthma Control Questionnaire scores (mean±SD, start to end of test: 2.8±1.4 to 1.4±0.9, p<0.0001) and sputum eosinophil counts (median (IQR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It should be noted that our analysis excluded some factors that were identified as predictors or risk factors for exacerbation in previous reports, such as race (ethnicity), longer duration of symptoms, or geographic region, as these factors may be confounded by correlations (e.g., collinearity) or described by a different hierarchical relationship (e.g., seasonal variation and geographic region) 39,40 . In addition, we had very limited information on type‐2 biomarkers, now known to be associated with the risk of exacerbations and the likelihood of a positive response to corticosteroids or biologics in severe asthma 41 . Interestingly, previous investigations have also indicated maintenance corticosteroid use as a predictor of asthma exacerbation, but have not disentangled it from the effect of individual baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that our analysis excluded some factors that were identified as predictors or risk factors for exacerbation in previous reports, such as race (ethnicity), longer duration of symptoms, or geographic region, as these factors may be confounded by correlations (e.g., collinearity) or described by a different hierarchical relationship (e.g., seasonal variation and geographic region) 39,40 . In addition, we had very limited information on type‐2 biomarkers, now known to be associated with the risk of exacerbations and the likelihood of a positive response to corticosteroids or biologics in severe asthma 41 . Interestingly, previous investigations have also indicated maintenance corticosteroid use as a predictor of asthma exacerbation, but have not disentangled it from the effect of individual baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, we believe that FeNO should ideally not be used as a standalone test to make treatment decisions, but should be combined with other simple measures of asthma control (e.g., ACQ), as most studies did. Whether addition of other noninvasive markers of asthma control that are mechanistically complimentary, such as blood eosinophils, can further improve outcomes is mostly unclear 28,34,35 …”
Section: Discussionmentioning
confidence: 99%
“…Whether addition of other noninvasive markers of asthma control that are mechanistically complimentary, such as blood eosinophils, can further improve outcomes is mostly unclear. 28,34,35 Over the past years, treatment with biologicals affecting the airway inflammatory pathways involved in asthma has rapidly emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent observational study evaluated the correlation between FeNO suppression after high-intensity corticosteroid therapy, asthma control, and sputum eosinophilia ( 53 ). They reported that persistently elevated FeNO despite corticosteroid therapy was associated with persistent sputum eosinophilia and worse control.…”
Section: Current Biomarkersmentioning
confidence: 99%